A systematic review and secondary data analysis of the interactions between the serotonin transporter 5-HTTLPR polymorphism and environmental and psychological factors in eating disorders. (January 2017) - Rozenblat, Vanja; Ong, Deborah; Fuller-Tyszkiewicz, Matthew; Akkermann, Kirsti; Collier, David; Engels, Rutger C.M.E.; Fernandez-Aranda, Fernando; Harro, Jaanus; Homberg, Judith R.; Karwautz, Andreas; Kiive, Evelyn; Klump, Kelly L.; et al.
Abstract: Objectives: To summarize and synthesize the growing gene x environment (GxE) research investigating the promoter region of the serotonin transporter gene (5-HTTLPR) in the eating disorders (ED) field, and overcome the common limitation of low sample size, by undertaking a systematic review followed by a secondary data meta-analysis of studies identified by the review. Method: A systematic review of articles using PsycINFO, PubMed, and EMBASE was undertaken to identify studies investigating the interaction between 5-HTTLPR and an environmental or psychological factor, with an ED-related outcome variable. Seven studies were identified by the systematic review, with complete data sets of five community ( n  = 1750, 64.5% female) and two clinical ( n  = 426, 100% female) samples combined to perform four secondary-data analyses: 5-HTTLPR x Traumatic Life Events to predict ED status ( n  = 909), 5-HTTLPR x Sexual and Physical Abuse to predict bulimic symptoms ( n  = 1097), 5-HTTLPR x Depression to predict bulimic symptoms ( n  = 1256), and 5-HTTLPR x Impulsiveness to predict disordered eating ( n  = 1149). Results: Under a multiplicative model, the low function (s) allele of 5-HTTLPR interacted with traumatic life events and experiencing both sexual and physical abuse (but not only one) to predict increased likelihood of an ED and bulimic symptoms, respectively. However, under an additive model there was also an interaction between sexual and physical abuse considered independently and 5-HTTLPR, and no interaction with traumatic life events. No other GxE interactions were significant. Conclusion: Early promising results should be followed-up with continued cross-institutional collaboration in order to achieve the large sample sizes necessary for genetic research.